Marches on Rome: Historical Events and Creative Transformations - Leake, Elizabeth (California Italian studies, 2024)
This paper, part of a larger project on unconventional forms of historiography, investigates a handful of cinematic and literary representations of life in Fascist Italy against the background of the March on Rome and, more in general, of Rome as the stage for the public display and embodiment of Fascist rhetoric. These texts can be grouped in three categories: 1) Fascist-era texts by supporters and opponents that express fear and pride; 2) later texts by march participants that express disappointment in the experience and the outcome of the march; and 3) more recent re-scriptings of the march as farce. The paper focusses particularly on the work performed by the second and third categories. These are not histories in the conventional sense but rather what we might call, with Edward Hallett Carr, “imaginative structures” through which unexpected and unexamined aspects of the past emerge, and in which memory works at once with and against history. Taking as a point of departure the idea that political history changes when we consider subjectivity, and that psychological elements are inextricable from the historical realm, I argue here that we have not fully understood the march until we take into account its experiential or affective qualities, which are most accessible to us through these unconventional sources. The insistent diminuzio anti-aulico of these texts—moving from the sublime to the disappointing to the absurd—marks their engagement with the notion of contingency, through which disappointment emerges and becomes operative. The paper argues that the march and its aesthetic iterations posit disappointment as an epistemological category—the way disappointment reinstates not simply experience but a very specific form of experience, as a way of knowing.